Light-trapped caddisflies to decipher the role of species traits and habitats in Hg accumulation and transfer. (January 2022) - Marle, Pierre; Timoner, Pablo; Liu, Wei; Castella, Emmanuel; Slaveykova, Vera I.
Abstract: We present a novel meta-community approach to explore the influence of species traits, such as adult body size, larval feeding type and microhabitat, as well as larval macrohabitat (main river channel vs. floodplain water bodies) on the concentration of total Hg accumulated ([THg]) in assemblages of adult caddisflies. We analyzed [THg] in 157 light-trapped adult caddisflies in a floodplain sector of the French upper Rhône River and used a linear mixed effect model to decipher the role of species traits and habitats in Hg accumulation. Variation of [THg] between species was best explained by the larval feeding type, whereas the contributions of adult size and larval micro and macro-habitat were minor. Results showed that [THg] in species associated with floodplain macrohabitats in the larval stage was lower than in those associated with the main river channel. This difference could depend on complexation of Hg by DOM (in the floodplain) and MES (in the main channel). This research provides a first evidence of the potential of an entire caddisfly assemblage for the assessment of contamination in large alluvial rivers. The implications of the results are discussed in view of the possible role of caddisflies as vectors of Hg to riparian predators. Graphical abstract: Image 1 Highlights: Variation of [THg] between species is best explained by the larval feeding type. Species [THg] depends also on their larval macrohabitat (main river channel vs floodplain). The most contaminated species are related to predators, filterers and sponge-feeders. Bioavailability of mercury could depend on complexation by DOM and MES.